Health status of primary school children: study from a rural health block of Lucknow - Abid Asghar, Syed; Gupta, Pratibha; Srivastava, Mrinal R.; Srivastava, J. P.; Zaidi, Zeashan H. (International Journal Of Community Medicine And Public Health, 2017)
Background: School health is an important branch of community health. School health services is an economical and powerful means of raising community health. In school child is vulnerable to stress, tension and endangerment of group life because all children are not the same and comes from different socioeconomic and cultural background and with different immunity status. Child is quite vulnerable at this growing age and hence become easy victims of many non-communicable diseases such as dental caries, anaemia, visual and hearing defects. The objective of the study was to assess health status of primary school children in rural areas of Lucknow. Methods: The present school-based descriptive cross-sectional study was conducted in the rural area of Lucknow from February to July 2015. Purposive sampling technique was adopted to select primary schools from 1st to 5th standard. All students who were present at the time of survey were included in the study. A pre-structured performa for each student was used to record information regarding anthropometric measurements, physical examination/ personal hygiene, clinical findings. Results: A total of 170 children were examined, among these 82 (48.23%) were boys and 88 (51.77%) were girls. Dental caries was the most common infirmity observed in 63 (37.05%) children with 95% CI (33.35- 40.75) and was statistically significant (p<0.05) with boys 29.27% and girls 44.31%. Anaemia were found in 65 (38.23%), boys were 32.92% and girls 43.18%. Ear discharge was seen in 17 (10%) children, boys were 6.10% and girls 13.63%. Conclusions: The common infirmity found were dental caries, anaemia and ear discharge. Effective strategy with good monitoring and evaluation is imperative in ensuring adequate and optimal implementation of school health services in primary schools in rural Lucknow.